Implementation of multicultural-based Islamic religious learning for students in the globalization era - Hamdan; Angga Saputra (Indonesian Journal of Learning and Educational Studies, 2025)
The aim of this research is to find out and analyze Implementation of multicultural-based Islamic religious learning for students in the era of globalization. This research method uses library  research used to collect data from various library sources relevant to the research topic. The data collection techniques employed by the researcher include documentation, with the researcher themselves serving as the core instrument. After the data is obtained, the researcher processes it by reading and analyzing it, then drawing conclusions. The findings of this study indicate that The application of multicultural-based Islamic religious learning to students can be implemented through: 1) preparing a Learning Plan, 2) the learning process takes place effectively through effective teaching.(effective teaching) and active learning (active learning), 3) Development of Islamic Religious Education Learning Materials based on multiculturalism and 4)Teacher competence in integrating multicultural values. This research provides a valuable contribution to the development of inclusive Islamic Religious Education learning strategies that are relevant to the multicultural context in Indonesia.